New genus of Steirodontini Brunner von Wattenwyl, 1878 (Orthoptera: Tettigoniidae: Phaneropterinae) from the Brazilian Amazon Rainforest - Mendes, Diego Matheus De Mello; Sobral, Rafael; Neto, Alberto Moreira Da Silva (Zootaxa, 2023)
The tribe Steirodontini (Phaneropterinae: Tettigoniidae) currently comprises five genera and 56 species, with its distribution restricted to the Neotropical region. In Brazil, four genera and 20 species of this tribe are recorded, all with records restricted to the Brazilian Southeast and South regions. This fact is a strong indication that the Brazilian fauna of this group is underestimated. In this work, the new monotypic genus Coronophyllum gen. nov. and the new species Coronophyllum catarinae sp. nov. from Amazonas, Brazil, are described and illustrated. Additionally, a map and comments on its distribution in an endemic area of the Brazilian Amazon are provided.